The low energy muon beam profile monitor for the muon g−2/EDM experiment at J-PARC. (4th September 2017) - Razuvaev, G.P.; Bae, S.; Choi, H.; Choi, S.; Ko, H.S.; Kim, B.; Kitamura, R.; Mibe, T.; Otani, M.
Abstract: The muon g −2 /EDM experiment at J-PARC aims to measure the muon anomalous magnetic moment and electric dipole moment with high precision by utilising an ultracold muon beam. The current muon g −2 discrepancy between the Standard Model prediction and the experimental value is about 3.5 standard deviations. This experiment requires a development of the muon LINAC to accelerate thermal muons to the 300 MeV/ c momentum. Detectors for beam diagnostics play a key role in such an experiment. The beam profile monitoring system has been designed to measure the profile of the low energy muon beam. It was tested during two beam tests in 2016 at the MLF D2 line at J-PARC. The detector was used with positive muons, Mu - ( μ + e − e − ), p and H -, e − and UV light. The system overview and preliminary results are given. Special attention is paid to the spatial resolution of the beam profile monitor and online monitor software used during data taking.